Geochemistry of Bagna and Stazka peat core from Poland - Lamentowicz, Mariusz (PANGAEA, 2021)
Geochemistry data of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.
Keywords: C-PEAT; Peatland